MAIN SOURCES FOR SCIENTIFIC RESEARCH. SCIENTIFIC LITERATURE IN LINGUISTICS AND LITERATURE (TAMADDUN NURI JURNALI, 2024)
Scientific research in the field of linguistics and literature plays a crucial role in the development of our understanding of language, communication and literary expression. This article aims to highlight the importance of scientific literature in these fields and explore the main sources that contribute to scientific discourse and knowledge dissemination.